Labour force paths as industry lingages: A perspective on clusters and industry life cycles - Mika Maliranta; Tuomo Nikulainen (The Research Institute of the Finnish Economy (ETLA), 2008)
We make several findings related to the dynamics of labour markets and industry life cycles in our analysis, which makes use of longitudinal employer-employee data that cover the whole working age population in Finland. Firstly, we find that across industry transitions of the employed are common. Secondly, employment transitions portray a network of industry linkages where specific industry clusters can be identified, as well as labour flow paths with long backward and forward linkages. Thirdly, most of the upstream labour mobility linkages are end up in the education industry, which thus seems to be an 'ancestor' of the most of the industries. On the other hand, we find eight totally isolated industries that had no distinct backward or forward linkages in the labour markets. Finally, we show that the labour flows are a significant indicator for industry life cycles.
Keywords: J23; J63; L16; 330; Employment transitions; industry clusters; industry life cycle; Arbeitsmarkt; Arbeitsmobilität; Industrie; Regionale Konzentration; Lebenszyklus; Finnland